PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PERTANAHAN NASIONAL DI KOTA MAKASSAR - Farhan Amiruddin; Burhanuddin Burhanuddin; Tenri Sayu Puspitaningsih Dipoatmodjo; Romansyah Sahabuddin; Uhud Darmawan Natsir (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to (1) Know the effect of organizational culture on employee performance, (2) Know the effect of job satisfaction on employee performance, (3) Know the effect of organizational culture and job satisfaction jointly on employee performance at the National Land Agency in Makassar City. The data used in this study are primary and secondary data with a sample size of 63 respondents. This research uses a quantitative approach and is analyzed using multiple linear regression analysis methods with the help of SPSS 25 data processing to prove three hypotheses. The results of this study prove that the Organizational Culture variable has a significant effect on Employee Performance, the value of t count> t table which is 3.193> t table of 1.671. The Job Satisfaction variable has a significant effect with a t value of 4.857> t table of 1.671. Simultaneously the organizational culture and job satisfaction variables on employee performance with F count of 17.935 this shows F count (17.935) > F table (3.150). Based on the results of this study, it is also known that the independent variables together or simultaneously have a significant effect on the dependent variable, namely employee performance at the National Land Agency in Makassar City. Therefore, if organizational culture and job satisfaction continue to be improved, it will certainly improve employee performance.